Hebrews, James - Morris, Leon Lamb, 1914-2006; Burdick, Donald W. (Grand Rapids, MI Zondervan, 1996)
Includes bibliographical references.
See also: The expositor's Bible commentary : with the New International Version at : 220.7 / GAE ; vol 12
Keywords: Bible. N.T. Hebrews -- commentaries; Bible. N.T. James -- commentaries